Analisis terhadap Krisis Regulasi Pengaturan Crypto Currency yang Mengancam Human Security di Indonesia - Thamrin, Djuni; Syauket, Amalia (Jurnal Keamanan Nasional, 2023)
The global economic landscape, particularly in Indonesia, is intricately linked to the realm of information technology. Cryptocurrency, often referred to as virtual or digital currency, is a product of financial technology (fintech) advancement and represents a disruptive innovation affecting various industries. Currently, the financial sector is particularly disrupted by the widespread use of cryptocurrency. However, the question arises as to whether the phenomenon of cryptocurrency is inherently illegal, warranting a negative label and posing a threat to human security when viewed from currency, legal, and economic perspectives. This research employs a qualitative descriptive approach, emphasizing secondary data obtained from diverse sources such as journal articles, conference papers, and relevant documents on cryptocurrency. The findings indicate that, within the Indonesian legal system, cryptocurrency cannot function as a means of payment due to its failure to fully meet the criteria of a currency. The utilization of cryptocurrency in quoting prices and conducting payments for goods and services contradicts currency laws. Nevertheless, cryptocurrency has acquired a clear legal attribute as a tradable commodity on futures exchanges. The ideal regulatory framework at present involves the creation of proportionate regulations, focusing on implementing antimoney laundering programs, addressing operational risks, and ensuring consumer protection. Striking a balance is crucial, as an inadequate regulatory environment not only jeopardizes economic welfare but also poses a significant threat to the core of human security.